Idiocnemis schorri sp. nov., a new damselfly species from southern Papua New Guinea (Odonata: Platycnemididae) - Gassmann, Dirk; Richards, Stephen J.; Polhemus, Dan A. (Zootaxa, 2016)
Idiocnemis schorri sp. nov. is described from the Hindenburg and Muller Ranges and the Kikori River Basin of southern Papua New Guinea. The new species differs from all congeners by, among other characters, a unique colour pattern on the thorax. Characters of males and females are illustrated and compared to those of similar species from the Idiocnemis bidentata group. The new species is found along small, shallow rainforest streams and is currently known only from the Trans-Fly Foreland and Papuan Gulf Foreland areas of endemism.